Benchmarking the Lean Six Sigma performance measures: a balanced score card approach. Issue 6 (5th August 2019) - Raval, Shruti J.; Kant, Ravi; Shankar, Ravi
Abstract : Purpose: The purpose of this paper is to develop the balance score card (BSC) approach based Lean Six Sigma (LSS) performance measurement system and investigate the critical measures currently practiced by Indian manufacturing organizations. Design/methodology/approach: This study offers insights of LSS performance measurement from manufacturing industry. Initially, the BSC-based framework is developed to recognize the adoption of LSS performance measures. Then, the framework is applied to nine Indian manufacturing organizations to assess the LSS performance measure practice. Findings: The BSC-based framework of LSS performance evaluation for manufacturing industry is formulated. Then, adoption of these LSS performance measures is investigated with nine Indian manufacturing organizations. The result indicates significant variability in terms of practicing level of LSS measures. However, the majority of organizations are more sensitive to the customer perspectives. Practical implications: This study reveals a background as to why the performance measurement is required for the success of LSS and for providing practical guidelines for designing performance metrics. The framework interrelates and captures various LSS perspectives and indicator measures, and furnishes a comprehensive outlook of the organization for strategic analysis. This study provides BSC-based template for performing the benchmarking study. This analysis may serve as a reference point for manufacturing organization to determine their system weaknesses, and assist them to concentrate on their most vital and suitable criteria and objectives. However, the analysis contributes to the knowledge on LSS performance measurement system and catches differences in theory and practice, paving the approach to newer research. Originality/value: This study renders an industry-oriented LSS performance measurement practical approach and suggests the easily adopted vital performance measures for different manufacturing organizations.